2012
DOI: 10.1016/j.drugalcdep.2011.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Employment-based reinforcement of adherence to an FDA approved extended release formulation of naltrexone in opioid-dependent adults: A randomized controlled trial

Abstract: Background Naltrexone provides excellent opioid blockade, but its clinical utility is limited because opioid-dependent patients typically refuse it. An injectable suspension of naltrexone for extended release (XR-NTX) was recently approved by the FDA for treatment of opioid dependence. XR-NTX treatment may require concurrent behavioral intervention to maximize adherence and effectiveness, thus we sought to evaluate employment-based reinforcement as a method of improving adherence to XR-NTX in opiate dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(113 citation statements)
references
References 28 publications
(33 reference statements)
7
95
1
5
Order By: Relevance
“…Some studies suggest that NTX may be useful for treating COC abuse (Kosten et al, 1989;McCaul and Svikis, 1996;Oslin et al, 1999;Schmitz et al, 2001;Comer et al, 2006) and others do not (Hersh et al, 1998;Schmitz et al, 2009;DeFulio et al, 2012;Dunn et al, 2012). In humans seeking treatment for COC dependence, NTX significantly increased the percentage of COC-negative urines among patients receiving 50 mg NTX plus relapse prevention therapy relative to those receiving 0 mg NTX plus relapse prevention, and those receiving 0 mg or 50 mg NTX plus drug counseling (Schmitz et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
“…Some studies suggest that NTX may be useful for treating COC abuse (Kosten et al, 1989;McCaul and Svikis, 1996;Oslin et al, 1999;Schmitz et al, 2001;Comer et al, 2006) and others do not (Hersh et al, 1998;Schmitz et al, 2009;DeFulio et al, 2012;Dunn et al, 2012). In humans seeking treatment for COC dependence, NTX significantly increased the percentage of COC-negative urines among patients receiving 50 mg NTX plus relapse prevention therapy relative to those receiving 0 mg NTX plus relapse prevention, and those receiving 0 mg or 50 mg NTX plus drug counseling (Schmitz et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
“…Combining XR‐NTX with employment‐based reinforcement has also been shown to be effective in unemployed adults 114. Others who may benefit include incarcerated persons and those without access to opioid agonist treatment 60, 71, 115.…”
Section: Current Approach To Treatment Of Opioid Use Disorder: Choosimentioning
confidence: 99%
“…For instance, all the preceding studies that have been conducted in the Therapeutic Workplace with opiate-dependent patients enrolled individuals who were receiving either methadone (Silverman et al, 2001; Silverman et al, 2002) or naltrexone (DeFulio et al, 2012; Dunn et al, 2013; Everly et al, 2011) to manage their opiate dependence. The successful results of these studies are consistent with a recent meta-analysis that reported opiate detoxification is most successful when a combination of pharmacological and psychosocial support is provided (Amato et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies inducted recently detoxified opioid-dependent patients onto oral naltrexone and then randomly assigned participants either to a contingency group that was required to accept oral naltrexone (Dunn et al, 2013), or a 6-dose course of sustained release naltrexone administered every 3 (Everly et al, 2011) or 4 (DeFulio et al, 2012) weeks to enter the workplace, or to a usual care condition that had access to the naltrexone product but could enter the workplace independent of naltrexone adherence. Results of all three studies showed improved adherence to naltrexone dosing in contingency versus control participants.…”
Section: Introductionmentioning
confidence: 99%